A Difference Equation of Banking Loan with Nonlinear Deposit Interest Rate - F. Hilal Gümüş; Moch. Fandi Ansori (Journal of Mathematical Sciences and Modelling)
This paper considers a banking loan model using a difference equation with a nonlinear deposit interest rate. The construction of the model is based on a simple bank balance sheet composition and a gradient adjustment process. The model produces two unstable loan equilibriums and one stable equilibrium when the parameter corresponding to the deposit interest rate is situated between its transcritical and flip bifurcations. Some numerical simulations are presented to align with the analytical findings, such as the bifurcation diagram, Lyapunov exponent, cobweb diagram, and contour plot sensitivity. The significance of our result is that the banking regulator may consider the lower and upper bounds for setting the nonlinear interest rate regulation and provide a control regulation for other banking factors to maintain loan stability.